Pelatihan Manajemen Pemasaran dan Pencatatan Keuangan Untuk Meningkatkan Daya Saing UMKM di Era Digital (Studi Kasus Pada UMKM Athira Bakery) : Pengabdian - Melis Dhea Saputri; Janah, Silvi Lailatul Nur; Bait, Jennifer Farihatul (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This community service program was implemented at Athira Bakery MSME to improve business competitiveness through digital marketing management training and financial record-keeping assistance. The main challenges faced by the business were the limited utilization of social media for promotion and the use of manual, unstructured financial records. The program applied a participatory approach involving observation, interviews, training, and direct mentoring. Digital marketing activities focused on social media account management, the development of engaging promotional content, and content scheduling. Financial management assistance introduced a simple digital bookkeeping system using Google Spreadsheets to record daily transactions, monthly summaries, and profit–loss reports. The results show an improvement in the owner’s understanding and skills in managing digital marketing and maintaining more systematic and accurate financial records. This program is expected to support more professional business management and enhance the sustainability of Athira Bakery MSME in the digital era. l requirement planning. Overall, this activity has helped partners improve their business management and operational efficiency, although the sustainability of the implementation still requires further assistance so that the benefits generated can continue to grow.